Research on ACO Algorithm Based on Scholarship Mechanism - Xia, Hui (Applied Mechanics and Materials, 2013)
Currently ,most of traditional Ant Colony Optimization algorithms that we are using were proved to be some critical issues, such as slow convergence and long time computation, search stagnation etc. A new improved ACO algorithm based on scholarship mechanism to balance between the search data processing and stagnation was addressed.Besides,the improved ACO alorithm was deeply analyzed and proved that the optimal solution can maintain ability for other path detection.The theoretical analysis and comparative experiments demonstrate that the imroved ACO has much better performance and can be used to solve the problems of convergence and search stagnation efficiently.